Exposure to copper metal enhances the tolerance of An. gambiae s.s. over multiple generations while reducing both fertility and fecundity in this primary malaria vector. [version 1; peer review: 1 approved, 2 approved with reservations] - Adam Gbankoto; Rousseau Djouaka; Camille Dossou; Louckman Monra Seidou; Ghislain T. Tepa-Yotto; Danahé Adanzounon; Genevieve Tchigossou; Innocent Djègbè; Aldo Emmanuel C. Glokpon; Massioudou Koto Yérima Gounou Boukari; Eric Tossou; Donald Hessou-Djossou (Wellcome Open Research)
Background Anopheles s.l. displays the potential to develop tolerance to heavy metals, particularly copper, this may occur at a significant biological cost, which can adversely affect its ecological fitness. This study investigated the larval metal exposure on larval development and reproduction of An. gambiae s.s., a laboratory susceptible strain, kisumu. Methods Stage 2 larvae of Anopheles gambiae, Kisumu were exposed to C1 = 484 μg L-1, C2 = 300 μg L-1 and 0 μg L-1 (control) of copper chloride. Larval mortality, pupation time, pupation rate, gonotrophic cycle length, fecundity and fertility of larvae/adults were assessed over six generations. Results Results revealed that larval mortality rate was significantly higher in the C1 groups of each group (p = 0.000), but this mortality rate decreased over generations. Pupation time was extended to 13 and 14 days respectively for C2 and C1 groups (p = 0.000) compared to the control group. Similar results were observed for the gonotrophic cycle, which increased from 4 days at G0 to more than 6 days at generation 5 in adults of C1. The pupation rate in generation 4 (C1) and generation 5 of the same group (p = 0.000) as well as the emergence rate in generation 4 (C2, p = 0.000) and generation 5 (C1 and C2, p = 0.000) decreased significantly compared to the control group. The average number of eggs laid was lower in the test groups from generation 4 to generation 5 (C1 and C2, p = 0.00) and egg fertility was also negatively affected by exposure of the larval stage of An. gambiae s.s. to copper. Conclusion Although studies have already shown that copper induces resistance in An. gambiae s.l. to insecticides, this study has shown that this adaptation requires a non-negligible biological cost in the life of the insect.